Humanin's impact on pain markers and neuronal viability in diabetic neuropathy model - Kelestemur, Muhammed Mirac; Bulut, Ferah; Bilgin, Batuhan; Hekim, Munevver Gizem; Adam, Muhammed; Ozcan, Sibel; Ozcan, Mete (Taylor & Francis Ltd, 2024)
Objective This study investigates the impact of chronic humanin (HN) treatment on pain-related markers (NMDA, substance P, TRPV1, and IL-1 beta) in diabetic mice's dorsal root ganglia (DRG). Additionally, we assess the effects of HN on cellular viability in DRG neurons. Methods In vivo experiments involved 15 days of HN administration (4 mg/kg) to diabetic mice (n = 10). Protein levels of NMDA, IL-1 beta, TRPV1, and substance P were measured in diabetic DRG. In vitro experiments explored HN's impact on apoptosis and cellular viability, focusing on the JAK2/STAT3 pathway. Results Humanin significantly reduced the elevated expression of NMDA, IL-1 beta, TRPV1, and substance P induced by diabetes (p < .05). Furthermore, HN treatment increased cellular viability in DRG neurons through JAK2/STAT3 pathway activation (p < .05). Conclusion These findings highlight the significance of understanding mitochondrial function and pain markers, as well as apoptosis in diabetes. The study provides insights for managing the condition and its complications.
Keywords: Humanin; dorsal root ganglia; pain markers; apoptosis; cell viability; diabetic neuropathy